1970
DOI: 10.1080/00288233.1970.10425396
|View full text |Cite
|
Sign up to set email alerts
|

Red phosphorus as a fertiliser for grass-clover pasture

Abstract: Red phosphorus, uncatalysed or catalysed with 2% copper (w/w), was compared with superphosphate as a fertiliser.Results showed;-(a) That the addition of uncatalysed red phosphorus to superphosphate did not prolong the fertilising effect of the mixture beyond that of superphosphate itself; (b) That red phosphorus was about 20-30% as effective as superphosphate when uncatalysed and 60% as effective when copper-catalysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Thus, Phi is stable under mildly reducing conditions that remove oxidants from solution (Figure 4). As stated earlier, oxidation of Phi to Pi is a relatively slow process [1,2]. Unfortunately, few studies document the influence of soil properties or conditions on Phi oxidation kinetics.…”
Section: Reduced Phosphorus Chemistry In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Phi is stable under mildly reducing conditions that remove oxidants from solution (Figure 4). As stated earlier, oxidation of Phi to Pi is a relatively slow process [1,2]. Unfortunately, few studies document the influence of soil properties or conditions on Phi oxidation kinetics.…”
Section: Reduced Phosphorus Chemistry In Soilmentioning
confidence: 99%
“…Although phosphate (Pi) fertilizers are initially soluble in soils, H 2 PO 4 − /HPO 4 2− adsorption and precipitation reactions can substantially reduce their availability to and recovery by crops. Reduced phosphorus (P) compounds containing phosphite (Phi) have been investigated since the 1930s as potential sources to meet P requirements of crops [1,2]. Because these early results demonstrated that H 2 PO 3 − /HPO 3 2− oxidation to plant available Pi was a slow process, few reduced P products were developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced phosphorus (P) compounds containing phosphite (Phi) have been investigated since the 1930s as potential sources to meet P requirements (MacIntire et. al., 1950;Jackman et. al., 1970).…”
Section: Introductionmentioning
confidence: 99%
“…По этой причине приобрели актуальность разработки методов детоксикации, которые можно использовать крупномасштабно -недорогих и без использования токсичных реагентов. Известны попытки применения элементного (белого и красного) фосфора в качестве фосфорного удобрения [Jackman et al, 1970;Rodriguez et al, 1972], но без большого успеха. В работе [Bohn et al, 1970] сообщается о естественной детоксикации белого фосфора в почве, однако авторы предполагают абиотическое окисление: исследования проводились на щелочных почвах, а в щелочной среде белый фосфор нестабилен даже в отсутствие кислорода.…”
Section: Introductionunclassified